PENGEMBANGAN TEMA DALAM BUKU AL-QIRA'AH AR-RASYIDAH UNTUK PELATIHAN MENULIS KREATIF BAHASA ARAB - Anis, Muhammad Yunus; Arifuddin, Arifuddin; Farhah, Eva (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2015)
Developing theme in a text of Arabic reading is the basis in a creative writing. By understanding the pattern of theme development in a text, beginner who wants to write in Arabic is easier in arranging the idea. This article is a research to see a great correlation between thematic progression with the creative writing in Arabic. The book taken as sample was al-Qirâ’ah al-Râsyidah which is used in MAN Karang Anyar and MAN 1 Surakarta. Related to the rheme in developing the theme, the students of both school wrote their daily activity by using thematic progression patterns. The result of the study showed that there is a great correlation between thematic progression pattern with the creative writing in Arabic.DOI: 10.15408/a.v2i2.2090